The educational grammar lesson in light of the relationship between language, mind, and the world (Journal of Human Sciences, 2023)
The instructional grammar lesson is considered one of the most important concerns for language enthusiasts as well as individuals and institutions. This is due to the deterioration and deviation that the Arabic language has experienced. The younger generation is no longer capable of mastering the language at the desired level or even at the minimum level. Therefore, the question of how to constantly renew the instructional grammar lesson has become a recurring one.Thus, the aim of this research is to present a conceptualization of a project for re-reading Arabic instructional grammar in light of the relationship between the world, the mind, and the language. Since the research idea originated from the reality of Arabic language learners, the first element in this research was related to identifying the most important reasons for the weakness in Arabic language proficiency among learners. The second element involved presenting the most significant previous experiences that have reinterpreted Arabic grammar in the light of heritage and modern linguistic theories.The third element addressed the essence of this research, which is to propose a project for re-reading Arabic grammar without completely disconnecting from heritage or previous experiments' achievements. The guiding idea of this research is that the mind perceives the world, and then language comes to describe the representation produced by this perception. Therefore, how does language form to correspond to the image of the world represented in?